The Effectiveness of Oil Palm Empty Bunch Compost and Goat Manure on Shallots Cultivated on Red Yellow Podzolic Soil - Mamondol, Marianne Reynelda; Meringgi, Amossius Rompolemba Andi Baso (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Red yellow podzolic (RYP) soil is one of the limiting factors in crop cultivation due to its high level of acidity and low content of essential nutrients. This study aimed to explore the effect of oil palm empty bunch (OPEB) compost and goat manure on shallots cultivated on RYP soil, determine the best treatment combination as fertilization recommendation, and analyze the economic feasibility for organic shallot farms. Observations were conducted on soil pH, crop growth, crop yield, shallot farm economic analysis, and the fertilization effectiveness calculation. The results demonstrated that the fertilization had a significant interaction effect on crop height, number of tillers, and fresh and dry tuber weights, but not on the soil pH, number of leaves, and tubers per cluster. A combination of 4 ton/ha compost and 1,00 ton/ha manure resulted in optimal production of dry tubers reaching 0.708 kg/plot (2.36 ton/ha). Meanwhile, the highest production of dry tubers of around 0.990 kg/plot (3.30 ton/ha) resulted from the combination of 5 ton/ha compost and 1.25 ton/ha manure. Farm analysis showed that organic fertilizer applications provided economic profit, indicated by R/C Ratio value greater than 1. The effectiveness of organic fertilization using compost and manure reached the highest values of 318.90% and 384%, respectively.